Association between plasma polyunsaturated fatty acids and depressive among US adults - Wang, Man; Yan, Xiaofang; Li, Yanmei; Li, Qian; Xu, Yingxia; Huang, Jitian; Gan, Juan; Yang, Wenhan (Frontiers in Nutrition, 2024)
Background: Depression is associated with greater functional impairment and high societal costs than many other mental disorders. Research on the association between plasma polyunsaturated fatty acids (PUFAs) levels and depression have yielded inconsistent results.Objective: To evaluate whether plasma n-3 and n-6 PUFAs levels are associated with depression in American adults.A cross-sectional study included 2053 adults (aged ≥ 20 y) in the National Health and Nutrition Examination Survey (NHANES), 2011-2012. The level of plasma n-3 and n-6 PUFAs were obtained for analysis. Self-reported Patient Health Questionnaire-9 (PHQ-9) was used to identify the depression status. Binary logistic regression analysis was performed to evaluate the association between quartiles of plasma n-3 and n-6 PUFAs and depression after adjustments for confounders.The study of 2053 respondents over 20 years of age with a weighted depression prevalence of 7.29% comprised 1043 men (weighted proportion, 49.13%) and 1010 women (weighted, 50.87%), with a weighted mean (SE) age of 47.58 (0.67) years. Significantly increased risks of depression over non-depression were observed in the third quartiles (OR = 1.65, 95% CI = 1.05-2.62) for arachidonic acid (AA; 20:4n-6); the third quartiles (OR = 2.20, 95% CI = 1.20-4.05) for docosatetraenoic acid (DTA; 22:4n-6); the third (OR = 2.33, 95% CI = 1.34-4.07), and highest quartiles (OR = 1.83, 95% CI = 1.03-3.26) for docosapentaenoic acid (DPAn-6; 22:5n-6); and the third (OR = 2.18, 95% CI = 1.18-4.03) and highest quartiles (OR = 2.47, 95% CI = 1.31-4.68) for docosapentaenoic acid (DPAn-3; 22:5n-3); the second (OR = 2.13, 95% CI = 1.24-3.66), third (OR = 2.40, 95% CI = 1.28-4.50), and highest quartiles (OR = 2.24, 95% CI = 1.08-4.69) for AA/docosahexaenoic acid (DHA; 22:6n-3) ratio compared with the lowest quartile after adjusting for confounding factors.Conclusions: Higher plasma levels of AA, DTA, DPAn-6, DPAn-3 PUFAs, and AA/DHA ratio may be potential risk factors for depression in US adults.